Future underground mining at LKAB Svappavaara: potential to combine caving and stoping methods - Sormunen, Matti; Saiang, David (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
Two of LKAB’s Svappavaara area open pit operations, Gruvberget and Leveäniemi, nestled between Kiruna and Malmberget SLC mines, have been initially considered for transition to underground mining using SLC or block caving methods. However, any underground mining operations at the Svappavaara site will be strongly influenced by external factors. For example, there are presently extremely tight constraints on ground deformation and land use, which are two factors that strongly discourage SLC and block caving methods. Therefore, it is necessary to investigate other alternative underground mining methods that can limit environmental disturbances while maintaining high productivity. Such alternatives may include combination of caving and stoping methods to create a form of hybrid method, with backfilling applied in this scenario. Such methods will decrease mining footprints associated with the cave mining methods. Hybrid mining methods and operations already exist but it is not well understood how they work and how they could be applied to suit more complex deposits. This paper considers the specific settings for the Svappavaara site and discusses how the concept of hybrid mining method can be applied in taking the Svappavaara orebodies underground. Funder: LKAB; ISBN för värdpublikation: 978-0-6450938-3-4